Defense Of Love Reflected In Lauren Oliver's Delirium Novel (2012) : A Psychoanalytic Approach - Pandansari, Ditta; , Drs. Abdillah Nugroho, M.Hum; , Siti Fatimah, S.Pd, M.Hum (2013)
The research is proposed to analyze the defense of love reflected in Delirium novel 2012 by A Psychoanalytic Approach. There are two objectives : the first is to analyze the novel in term of structural elements, and the second is to analyze the novel based on the Psychoanalytic Approach. This study is a qualitative study, using Lauren Oliver's Delirium novel 2012 as of structural elements, and the secondary data. The primary data source is Delirium novel which is directed by Lauren Oliver, and the secondary data are some articles, book and articles, accessing internet, taking notes of important part, arranging, and drawing conclusion the data. In analyzing the data, the writer employs descriptive analysis. The outcome of the study shows that the novel illustrates how to get a beautiful feeling of love, it proves that love has no gender, true love is not a disease. Defense of love is not easy, but if it can be gotten, it will make happy for everyone in their relationship.